Photodynamic inactivation strategies for maximizing antifungal effect against Sporothrix spp. and Candida albicans in an in vitro investigation. - Amanda Regina Rocha; Natalia Mayumi Inada; Ana Paula da Silva; Vanderlei Salvador Bagnato; Hilde Harb Buzzá (PLoS Neglected Tropical Diseases)
Background Sporotrichosis is a zoonotic disease caused by the dimorphic fungus Sporothrix spp., leading to skin lesions that can, in some cases, progress and result in the death of infected individuals. Candida albicans is another fungus involved in several skin, oral, and vaginal mucosal infections. Fungal diseases are concerning due to increasing incidence and the limited variety of antifungal classes available for treatment. Furthermore, antifungal medications can cause various side effects, exacerbated by their prolonged use during infection treatment. There is a need to explore alternatives to conventional drugs that are effective, fast, and safe in combating sporotrichosis. This study aimed to achieve in vitro elimination of the fungi Sporothrix brasiliensis and Sporothrix schenckii through Photodynamic Inactivation (PDI), using curcumin as a photosensitizer and in combination with antifungal agents used in the treatment of sporotrichosis. Methodology Yeasts of Candida albicans, Sporothrix brasiliensis, and Sporothrix schenckii were subjected to Photodynamic Inactivation (PDI) using light at a wavelength of 450 ± 10 nm, irradiance of 35 mW/cm2, delivering a fluence of 31.5 J/cm2, with curcumin as the photosensitizer at doses ranging from 0.75 to 150 μg/mL. After determining the Minimum Inhibitory Concentration (MIC) values of the antifungal drugs itraconazole, ketoconazole, and potassium iodide, sub-MIC doses of these antifungals were combined with sub-MIC doses of curcumin in a new PDI session. Conclusion Photodynamic inactivation is a promising technique in the treatment of sporotrichosis, as well as its combination with antifungals. The combination of curcumin in concentrations ranging from 0.75 g/mL a 7.5 g/mL with sub-MIC concentrations of itraconazole, ketoconazole, and potassium iodide was able to completely inactivate the fungi C. albicans, S. brasiliensis and S. schenckii, indicating that PDI may increase the effectiveness of antifungals. However, further studies are needed to establish protocols for future clinical applications.